Deficits in voice and multisensory processing in patients with Prader-Willi syndrome. (May 2016) - Salles, Juliette; Strelnikov, Kuzma; Carine, Mantoulan; Denise, Thuilleaux; Laurier, Virginie; Molinas, Catherine; Tauber, Maïthé; Barone, Pascal
Abstract: Prader-Willi syndrome (PWS) is a rare neurodevelopmental and genetic disorder that is characterized by various expression of endocrine, cognitive and behavioral problems, among which a true obsession for food and a deficit of satiety that leads to hyperphagia and severe obesity. Neuropsychological studies have reported that PWS display altered social interactions with a specific weakness in interpreting social information and in responding to them, a symptom closed to that observed in autism spectrum disorders (ASD). Based on the hypothesis that atypical multisensory integration such as face and voice interactions would contribute in PWS to social impairment we investigate the abilities of PWS to process communication signals including the human voice. Patients with PWS recruited from the national reference center for PWS performed a simple detection task of stimuli presented in an uni-o or bimodal condition, as well as a voice discrimination task. Compared to control typically developing (TD) individuals, PWS present a specific deficit in discriminating human voices from environmental sounds. Further, PWS present a much lower multisensory benefits with an absence of violation of the race model indicating that multisensory information do not converge and interact prior to the initiation of the behavioral response. All the deficits observed in PWS were stronger for the subgroup of patients suffering from Uniparental Disomy, a population known to be more sensitive to ASD. Altogether, our study suggests that the deficits in social behavior observed in PWS derive at least partly from an impairment in deciphering the social information carried by voice signals, face signals, and the combination of both. In addition, our work is in agreement with the brain imaging studies revealing an alteration in PWS of the "social brain network" including the STS region involved in processing human voices. Highlights: Patients with Prader Willi symptoms (PWS) display altered social interactions. PWS present deficit to process human voice and visuo-auditory integration. Our results are in agreement with an alteration of the Social Brain in PWS.